2021
DOI: 10.3390/microorganisms9061308
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Properties of Fluoroquinolone-Resistant, qnr-Carrying Escherichia coli Isolated from the German Food Chain in 2017

Abstract: Fluoroquinolones are the highest priority, critically important antimicrobial agents. Resistance development can occur via different mechanisms, with plasmid-mediated quinolone resistance (PMQR) being prevalent in the livestock and food area. Especially, qnr genes, commonly located on mobile genetic elements, are major drivers for the spread of resistance determinants against fluoroquinolones. We investigated the prevalence and characteristics of qnr-positive Escherichia (E.) coli obtained from different monit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…7,21,22 Although the main cause of quinolones resistance is a mutation in chromosomal topoisomerases, PMQR genes have been believed that play a significant role in the development of quinolone-resistant isolates due to their high horizontal transferability. 23 This study reports the high prevalence (88%) of PMQR genes in isolates, in which aac(6ʹ)-Ib-cr was detected as the most common gene. These results are in line with other studies conducted in Iraq, 7 Iran, 24 Korea, 25 and Thailand.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…7,21,22 Although the main cause of quinolones resistance is a mutation in chromosomal topoisomerases, PMQR genes have been believed that play a significant role in the development of quinolone-resistant isolates due to their high horizontal transferability. 23 This study reports the high prevalence (88%) of PMQR genes in isolates, in which aac(6ʹ)-Ib-cr was detected as the most common gene. These results are in line with other studies conducted in Iraq, 7 Iran, 24 Korea, 25 and Thailand.…”
Section: Discussionmentioning
confidence: 79%
“…On a worldwide scale, the prevalence rate of quinolones resistance in K. pneumoniae isolates might be differed by geographic area; for example, resistance rates in Togo are 85.8%, 62.8% in Iraq, and 34.8% in Iran 7,21,22 . Although the main cause of quinolones resistance is a mutation in chromosomal topoisomerases, PMQR genes have been believed that play a significant role in the development of quinolone‐resistant isolates due to their high horizontal transferability 23 …”
Section: Discussionmentioning
confidence: 99%
“…Resistance development against fluoroquinolones can occur via various mechanisms ranging from chromosomal gene mutations to the specific transferable genes acquisition (28). The mutations in the chromosomal elements encoding the target enzyme (quinolone resistance determining region, QRDR) DNA gyrase (gyrA, gyrB) and topoisomerase IV (parC, parE) can considerably alter the susceptibility of the isolates, while the acquisition specific genes are always involved in overexpression of efflux pumps, alteration of the membrane permeability, and the expression of inactivation enzymes (28)(29)(30). Since foreign plasmids were not acquired in the genome, the acquired horizontal transfer of quinolone resistant genes was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on commensal and ESBL-producing E. coli from the German monitoring on zoonoses from livestock and food, the occurrence of qnr genes in fluoroquinolone-/quinolone-resistant E. coli was determined. Similar to the Korean E. coli, Juraschek et al [8] also found a high number of fluoroquinolone-/quinolone-resistant isolates among ESBL-producing E. coli from livestock and food origin. So, the occurrence of E. coli co-carrying genes for both antibiotic classes seem to emerge.…”
mentioning
confidence: 84%